1991
DOI: 10.3102/01623737013002189
|View full text |Cite
|
Sign up to set email alerts
|

School Size, Characteristics, and Outcomes

Abstract: To investigate school size effects for secondary schools, 18 school outcomes, including the average scores on state-developed tests, student retention, suspensions, postschool employment, and college attendance for 293 public secondary schools in New Jersey were regressed on 23 school characteristics, including district socioeconomic status and percentages of students from low-income families; school size and number of schools within each district; and teacher characteristics encompassing salaries, degree stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(26 citation statements)
references
References 13 publications
(14 reference statements)
2
20
0
Order By: Relevance
“…While size itself has no correlation with achievement, the interaction between size and SES (measured as the product of the two) as an explanatory variable has been found to be significant in studies in Alaska, California, and West Virginia (Rural Challenge 1999). The use of this interaction term has confirmed that smaller schools have positive effects for impoverished students, a phenomenon that may in part be due to the fact that smaller schools have been linked to higher levels of participation in extracurricular activities (Fowler 1992;Cotton 1996), higher attendance rates (Fowler and Walberg 1991;Fowler 1992) and fewer behavioral problems (Stockard and Mayberry 1992). Based on these findings, the closing of small schools in poor rural areas would seem to be ill-advised and counterproductive, and in fact would probably compound the problem of delivering quality education to poor students (Walberg and Fowler 1987;Huang and Howley 1993).…”
Section: Consolidation and Student Achievementmentioning
confidence: 68%
“…While size itself has no correlation with achievement, the interaction between size and SES (measured as the product of the two) as an explanatory variable has been found to be significant in studies in Alaska, California, and West Virginia (Rural Challenge 1999). The use of this interaction term has confirmed that smaller schools have positive effects for impoverished students, a phenomenon that may in part be due to the fact that smaller schools have been linked to higher levels of participation in extracurricular activities (Fowler 1992;Cotton 1996), higher attendance rates (Fowler and Walberg 1991;Fowler 1992) and fewer behavioral problems (Stockard and Mayberry 1992). Based on these findings, the closing of small schools in poor rural areas would seem to be ill-advised and counterproductive, and in fact would probably compound the problem of delivering quality education to poor students (Walberg and Fowler 1987;Huang and Howley 1993).…”
Section: Consolidation and Student Achievementmentioning
confidence: 68%
“…Luyten (1994), for example, estimates a number of hierarchical linear models for the USA, Sweden and the Netherlands but finds that school size is not significantly related to achievement in mathematics and science, whereas Heck and Mayer (1993) find that school size is negatively related to a number of outcomes, including maths score, reading score and attendance. Deller and Rudnicki (1993) and Fowler and Walberg (1991) also find evidence of an inverse relationship between school size and school outcomes. More recently, Sander (1994) finds strong evidence of a positive relationship in his study of schools in Chicago, but Lamdin (1995) finds no evidence of any relationship for schools in Baltimore.…”
Section: School Sizementioning
confidence: 81%
“…Student socio-economic status, and family and racial/ethnic background (Coleman et al, 1966;Fowler and Walberg, 1991;Gottfredson et al, 2005;Hanushek, 1997;Rouse and Barrow, 2006;Rumberger and Palardy, 2005;Welsh, 2001), school enrollment size (Cotton, 1996;Ready et al, 2004;Schneider, 2002;Williams, 1990), and building age (Earthman and Lemasters, 1996;Kumar et al, 2008;McGuffey, 1982;National Research Council, 2006;Schneider, 2002;Uline, 2000) have repeatedly been shown to be strongly related to student academic achievement and misbehaviors. Due to their strong connection with student performance, these following four aggregate factors for each school were accounted for in the statistical analyses conducted in this study.…”
Section: Control Variables: Four Important Factors Related To Studentmentioning
confidence: 95%